Pengembangan Buku Pengayaan Menyusun Teks Biografi Bermuatan Karakter Wirausaha untuk Peserta Didik Kelas X SMK - Anwar, Chusnul (Lingua, 2020)
This study aims to develop the enrichment book on writing biography text containing entrepreneurial character for tenth graders of Vocational High School. This study uses research and development (R&D) approach. The result shows that the prototype achieved very good judgment from the experts with the mean score 89.1 on the material aspect, 87.5 on the material presentation aspect, 85.4 on the language aspect, 80.4 on the graphic aspect, and 87.5 on the aspect of entrepreneurial character content.